Lithium supplement agent and preparation method thereof, positive pole piece and secondary battery
By covering the composite vanadium phosphate material on the surface of lithium-rich lithium ferrate material, the poor air stability and safety of lithium-rich positive electrode materials during lithium replenishment are solved, and the stability and safety of lithium-rich positive electrodes are improved and the electrochemical performance of the positive electrode sheet and secondary batteries are improved.
Patent Information
- Application Number
- CN202411978536.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-28
AI Technical Summary
The existing lithium-rich cathode materials have poor air stability and safety problems during the lithium replenishment process, which limits their application.
By coating the composite lithium vanadium phosphate material on the surface of the lithium-rich lithium ferrate material, it prevents its contact with air, improves the stability and safety of lithium supplement agents, while providing electrical conductivity and capacity.
It significantly improves the stability and safety of lithium supplements and improves the electrochemical performance of positive electrode sheets and secondary batteries.
Smart Images

Figure CN119725490A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of energy storage technology, and in particular to a lithium supplement and a preparation method thereof, a positive electrode sheet and a secondary battery. Background Art
[0002] Lithium-ion batteries are widely used in energy storage fields such as new energy vehicle batteries. During the first charging process of lithium-ion batteries, the organic electrolyte will permanently consume a large amount of lithium from the positive electrode, and reduce and decompose on the surface of the negative electrode such as graphite to form a solid electrolyte interphase (SEI) film, resulting in a low Coulombic efficiency (CE) in the first cycle, reducing the capacity and energy density of the lithium-ion battery.
[0003] In view of the low coulombic efficiency of lithium-ion batteries and the reduced capacity and energy density of lithium-ion batteries, lithium replenishment is needed to make up for the irreversible loss of lithium. At present, the main methods of lithium replenishment are negative electrode lithium replenishment and positive electrode lithium replenishment. Compared with the difficulty and large investment of negative electrode lithium replenishment, positive electrode lithium replenishment is easy to operate and has a simple process. There is no need to change the production line structure. It only needs to add lithium replenisher in the positive electrode slurry mixing link, which has good application prospects. The ideal positive electrode lithium replenisher needs to meet multiple conditions, such as good air stability, high specific energy and volume energy density, lithium desorption potential and lithium insertion potential between the working potential of the positive electrode material, and compatibility with the current common manufacturing process and battery system.
[0004] Currently, the common positive electrode lithium supplements are mainly lithium-rich positive electrode materials, such as lithium-rich lithium iron oxide and lithium-rich lithium nickel oxide. However, these lithium-rich positive electrode materials have problems such as poor air stability, easy release of oxygen during lithium supplementation, and relatively poor safety. Summary of the invention
[0005] In view of the technical problems existing in the background technology, the present application provides a lithium supplement and a preparation method thereof, a positive electrode plate and a secondary battery, aiming to solve the technical problems of poor stability and safety of lithium-rich positive electrode materials in the related technology.
[0006] In a first aspect, an embodiment of the present application provides a lithium supplement, comprising: a lithium-rich material, the lithium-rich material comprising a core and a coating layer coated on the surface of the core; wherein the core comprises: a lithium-rich lithium ferrate material, and the material of the coating layer comprises: a composite lithium vanadium phosphate material.
[0007] In the technical solution of the embodiment of the present application, a composite lithium vanadium phosphate material is coated on the surface of a lithium-rich lithium ferrate material. The composite lithium vanadium phosphate material protects the lithium-rich lithium ferrate material, hinders the contact between the lithium-rich lithium ferrate material and the air, and is beneficial to improving the stability and safety of the lithium supplement. At the same time, compared with the carbon material coated on the surface of the lithium-rich lithium ferrate material, the composite lithium vanadium phosphate material not only has better conductivity, but also provides partial capacity, thereby effectively improving the stability and safety of the lithium-rich lithium ferrate material, while also providing ion conduction channels and capacity, significantly improving the lithium supplement effect, and thereby improving the electrochemical performance of the positive electrode plate, secondary battery and electrical device using the lithium supplement.
[0008] In some embodiments, the lithium-rich material has the general formula Li x FeO y @Li m V 2 (PO 4 ) p (P 2 O 7 ) q , where x is 5.05~5.2, y is 4.025~4.1, m is 3.02~3.05, p is 1.4~1.6, and q is 0.8~1.4.
[0009] In the above embodiment, the composite lithium vanadium phosphate material of the coating layer of the lithium-rich material contains both pyrophosphate and phosphate while providing ion channels and capacity, and the ratio of the two is appropriate. The ionic conductivity of the composite lithium vanadium phosphate material is improved by doping with anions, and the water absorption of pyrophosphate is utilized to avoid hydrolysis of the lithium-rich lithium ferrite material due to water absorption and the sharp attenuation of the electrochemical performance, which is beneficial to improving the lithium supplement effect.
[0010] In some embodiments, the molar ratio of the lithium-rich lithium ferrite material to the composite lithium vanadium phosphate material is 1:(0.05-0.3).
[0011] In the above embodiment, by controlling the amount ratio of the lithium-rich lithium iron oxide material to the composite lithium vanadium phosphate material within the range of 1: (0.05-0.3), the ratio of the core to the coating layer of the lithium supplement agent is appropriate, and the protective effect of the coating layer on the core is fully utilized to improve the stability of the lithium supplement agent while maintaining a high capacity of the lithium supplement agent.
[0012] In a second aspect, the present application provides a method for preparing a lithium supplement, comprising:
[0013] Provide the kernel;
[0014] Forming a coating layer on the surface of the inner core to obtain a lithium supplement;
[0015] The lithium supplement comprises a core and a coating layer coated on the surface of the core, the core comprises a lithium-rich lithium ferrite material, and the material of the coating layer comprises a composite lithium vanadium phosphate material.
[0016] In the technical solution of the embodiment of the present application, a coating layer is formed on the surface of the lithium-rich ferrite material, and the material of the coating layer includes: a composite lithium vanadium phosphate material. By coating the composite lithium vanadium phosphate material on the surface of the lithium-rich ferrite material, the composite lithium vanadium phosphate material protects the lithium-rich ferrite material, hinders the contact between the lithium-rich ferrite material and the air, and is beneficial to improve the stability and safety of the lithium supplement; at the same time, compared with the carbon material coated on the surface of the lithium-rich ferrite material, the composite lithium vanadium phosphate material not only has better conductivity, but also provides partial capacity, thereby effectively improving the stability of the lithium-rich ferrite material, while also providing ion conduction channels and capacity, significantly improving the lithium supplement effect, and thereby improving the electrochemical performance of the positive electrode sheet, secondary battery and electrical device using the lithium supplement. At the same time, the preparation method of forming the composite lithium vanadium phosphate material on the surface of the lithium-rich ferrite material is simple and easy to implement.
[0017] In some embodiments, a kernel is provided, comprising:
[0018] The first lithium salt and the first iron source are mixed and subjected to a first calcination treatment to obtain the lithium-rich lithium ferrite material;
[0019] Wherein, the first lithium salt includes: at least one of lithium sulfite and lithium bisulfite, and the first iron source includes: at least one of red iron oxide, iron oxyhydroxide, iron hydroxide, ferrous oxalate and ferric citrate.
[0020] In the above embodiment, the above lithium salt is used as the raw material of the first lithium salt. Compared with other lithium sources such as lithium oxide and lithium carbonate, the cost is lower and the decomposition temperature is lower, thereby avoiding the problem of insufficient purity caused by absorbing the decomposition gas when synthesizing lithium-rich lithium iron oxide at high temperature.
[0021] In some embodiments, the step of forming a coating layer on the surface of the core to obtain a lithium supplement comprises:
[0022] Providing a dispersion liquid having the lithium-rich lithium ferrite material;
[0023] Dissolving the second lithium salt, the first vanadium salt and the pyrophosphate source in the dispersion, and subjecting the dispersion to a first drying process to obtain a first material;
[0024] The first material is subjected to a second calcination treatment to obtain the lithium supplement agent;
[0025] The second lithium salt includes at least one of lithium acetate, lithium gluconate and lithium nitrate, the first vanadium salt includes at least one of vanadium chloride and vanadium acetate, and the pyrophosphate source includes at least one of pyrophosphate, ammonium monohydrogen pyrophosphate and ammonium dihydrogen pyrophosphate.
[0026] In the above embodiment, a dispersion liquid having a lithium iron rich material is prepared, and a second lithium salt, a first vanadium salt and a pyrophosphate source are dissolved in the dispersion liquid, and then a first drying treatment is performed. On the one hand, the second lithium salt, the first vanadium salt and the pyrophosphate source are uniformly mixed with the lithium iron rich material in the form of a solution. On the other hand, the first drying treatment is used to remove the solvent, so that the second lithium salt, the first vanadium salt and the pyrophosphate source are mixed and uniformly wrapped on the surface of the lithium iron rich material, and a mixed material layer of the second lithium salt, the first vanadium salt and the pyrophosphate source is formed on the surface of the lithium iron rich material, so that the second lithium salt, the first vanadium salt and the pyrophosphate source can be easily coated by in-situ sintering in the second calcination treatment. When the above-mentioned second lithium salt, first vanadium salt and pyrophosphate source materials are used, it is beneficial for the gas generated by the reaction to volatilize at a lower temperature during the second calcination treatment. At the same time, the above-mentioned pyrophosphate source material is used to participate in the preparation of the composite lithium vanadium phosphate material, which absorbs part of the water vapor to become phosphate during the second calcination treatment. While obtaining the anion-doped composite lithium vanadium phosphate material, the water vapor in the atmosphere is effectively dried, avoiding the hydrolysis of the lithium-rich lithium ferrite material due to water absorption, which is beneficial to effectively improve the lithium replenishment effect of the lithium replenisher.
[0027] In some embodiments, during the first calcination treatment, the method for preparing a lithium supplement further includes: removing waste gas generated by the first calcination treatment so that the humidity of the first calcination treatment is ≤0.5%; and / or,
[0028] After dissolving the second lithium salt, the first vanadium salt and the pyrophosphate source in the dispersion, the preparation method of the lithium supplement further comprises: grinding the dispersion so that the particle size of the lithium-rich lithium ferrite material in the dispersion is 300nm~500nm; and / or,
[0029] During the second calcination treatment, the preparation method of the lithium supplement further includes: removing waste gas generated by the second calcination treatment so that the humidity of the second calcination treatment is ≤0.5%.
[0030] In the above embodiment, controlling the humidity of the first calcination treatment and promptly removing the waste gas generated during the first calcination treatment is beneficial to improving the stability and purity of the lithium-rich ferrite material. Controlling the particle size of the lithium-rich ferrite material after grinding to be within 300nm~500nm, obtaining a lithium-rich ferrite material with a small particle size and a concentrated particle size distribution, facilitating the uniform deposition of the blended material layer on the surface of the lithium-rich ferrite material, thereby facilitating obtaining a lithium supplement agent with uniform and complete coating. Controlling the humidity of the second calcination treatment and promptly removing the waste gas generated during the second calcination treatment is beneficial to reducing the contact between oxygen, water vapor and waste gas generated by the reaction and the lithium supplement agent in the second calcination treatment, improving the purity and stability of the lithium supplement agent, and thus improving the lithium supplement effect of the lithium supplement agent.
[0031] In some embodiments, the preparation method of the lithium supplement meets at least one of the following conditions:
[0032] (1) The molar ratio of the lithium element in the first lithium salt to the iron element in the first iron source is (5.05-5.2):1;
[0033] (2) The temperature of the first calcination treatment is 400°C to 600°C, and the time is 4h to 12h;
[0034] (3) The oxygen content of the first calcination treatment is less than 100 ppm, and the oxygen content of the second calcination treatment is less than 500 ppm;
[0035] (4) the molar ratio of the lithium element in the second lithium salt, the vanadium element in the first vanadium salt and the pyrophosphate ion in the pyrophosphate source is (3.02-3.05):2:(1.5-1.6);
[0036] (5) The first drying process is spray drying;
[0037] (6) The water content of the solvent used in the dispersion is less than 100 ppm;
[0038] (7) The temperature of the second calcination treatment is 600°C to 700°C, and the time is 3 h to 6 h.
[0039] In the above embodiment, the molar ratio of the lithium element in the first lithium salt to the iron element in the first iron source is controlled within the above range, so that the first lithium salt and the first iron source can fully react to obtain lithium-rich lithium ferrite. Controlling the temperature, reaction time and oxygen content of the first calcination treatment is conducive to avoiding the lithium-rich lithium ferrite material from absorbing the gas generated during the first calcination treatment or reacting with oxygen at a higher temperature while the lithium-rich lithium ferrite material is fully generated, thereby facilitating the improvement of the purity and stability of the lithium supplement. By controlling the molar ratio of the lithium element in the second lithium salt, the vanadium element in the first vanadium salt and the pyrophosphate in the pyrophosphate source to (3.02~3.05):2:(1.5~1.6), it is conducive to the full reaction of the three to obtain a composite lithium vanadium phosphate material. The first drying treatment using spray drying is conducive to effective control of the particle size of the first material. Controlling the water content of the solvent used in the dispersion to be less than 100ppm, reducing the introduction of water, and helping to avoid the hydrolysis of the lithium-rich lithium ferrite material and the attenuation of the electrochemical performance. The temperature, time and oxygen content of the second calcination treatment are controlled, and while the composite lithium vanadium phosphate material fully reacts to form a coating layer, the contact between oxygen and the lithium supplement agent in the second calcination treatment is reduced, which is beneficial to improving the stability and purity of the lithium supplement agent.
[0040] In a third aspect, an embodiment of the present application provides a positive electrode plate, including a current collector, and a positive electrode material disposed on at least one side of the current collector along its thickness direction, wherein the positive electrode material includes the lithium supplement agent as described in the first aspect.
[0041] In this embodiment, the positive electrode plate contains the above-mentioned lithium supplement agent, which includes: a lithium-rich lithium iron oxide material and a composite lithium vanadium phosphate material coated on the surface of the lithium-rich lithium iron oxide material. The composite lithium vanadium phosphate material protects the lithium-rich lithium iron oxide material, hinders the contact between the lithium-rich lithium iron oxide material and the air, which is beneficial to improving the stability and safety of the lithium supplement agent; at the same time, compared with the carbon material coated on the surface of the lithium-rich lithium iron oxide material, the composite lithium vanadium phosphate material not only has better conductivity, but also provides partial capacity, thereby effectively improving the stability of the lithium-rich lithium iron oxide material while also providing ion conduction channels and capacity, significantly improving the lithium supplement effect, and therefore, is beneficial to improving the electrochemical performance of the positive electrode plate.
[0042] In a fourth aspect, an embodiment of the present application provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator, wherein the positive electrode sheet is the positive electrode sheet as described in the third aspect.
[0043] In this embodiment, the secondary battery includes the above-mentioned positive electrode plate. Since the lithium replenisher in the positive electrode plate has significantly improved lithium replenishment effect, stability and safety, the performance of the secondary battery in terms of capacity, stability, etc. are all improved.
[0044] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0046] Figure 1 A schematic flow chart of a method for preparing a lithium supplement provided in an embodiment of the present application. DETAILED DESCRIPTION
[0047] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0048] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0049] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0050] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0051] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0052] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0053] In the description of the embodiments of the present application, the technical terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, which are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the embodiments of the present application.
[0054] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, and it can be the internal connection of two elements or the interaction relationship between two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.
[0055] The lithium-rich cathode materials currently used, such as lithium-rich nickel oxide (Li 2 NiO 2 ) and lithium-rich iron oxide (Li 5 FeO 4 ) can all be used to supplement lithium, but these materials have problems such as poor air stability and easy release of oxygen, which leads to poor safety, limiting their application as lithium supplement materials.
[0056] In order to solve the technical problems of poor stability and safety of lithium-rich positive electrode materials in the related art, the present application provides a lithium supplement agent and a preparation method thereof, a positive electrode plate and a secondary battery, wherein a composite lithium vanadium phosphate material is coated on the surface of the lithium-rich positive electrode material, the composite lithium vanadium phosphate material protects the lithium-rich lithium ferrate material, hinders the contact between the lithium-rich lithium ferrate material and the air, and is beneficial to improving the stability and safety of the lithium supplement agent; at the same time, compared with the carbon material coated on the surface of the lithium-rich lithium ferrate material, the composite lithium vanadium phosphate material not only has better conductivity, but also provides partial capacity, thereby effectively improving the stability of the lithium-rich lithium ferrate material while providing ion conduction channels and capacity, significantly improving the lithium supplement effect, and thereby improving the electrochemical performance of the positive electrode plate, secondary battery and electrical device using the lithium supplement agent.
[0057] In a first aspect, an embodiment of the present application provides a lithium supplement, which includes: a lithium-rich material, the lithium-rich material includes a core and a coating layer coated on the surface of the core; wherein the core includes a lithium-rich lithium ferrate material, and the material of the coating layer includes: a composite lithium vanadium phosphate material.
[0058] The composite lithium vanadium phosphate material is a polyanion material that can provide a portion of the capacity and has good electronic conductivity and ionic conductivity.
[0059] By coating the surface of the lithium-rich lithium iron phosphate material with a composite lithium vanadium phosphate material, the composite lithium vanadium phosphate material protects the lithium-rich lithium iron phosphate material, hinders the contact between the lithium-rich lithium iron phosphate material and the air, which is beneficial to improving the stability and safety of the lithium supplement; at the same time, compared with the carbon material coated on the surface of the lithium-rich lithium iron phosphate material, the composite lithium vanadium phosphate material not only has better conductivity, but also provides partial capacity, thereby effectively improving the stability and safety of the lithium-rich lithium iron phosphate material, while also providing ion conduction channels and capacity, significantly improving the lithium supplement effect.
[0060] In some embodiments, the lithium-rich material has the general formula Li x FeO y @Li m V 2 (PO 4 ) p (P 2 O 7 ) q , where x is 5.05~5.2, y is 4.025~4.1, m is 3.02~3.05, p is 1.4~1.6, and q is 0.8~1.4.
[0061] Among them, Li x FeO y Represents lithium iron oxide-rich material, Li m V 2 (PO4 ) p (P 2 O 7 ) q Indicates the material of the coating.
[0062] For example, x can be 5.05, 5.1, 5.12, 5.15, 5.18 or 5.2, etc., and y can be 4.025, 4.028, 4.03, 4.035, 4.04, 4.045, 4.05, 4.055, 4.058, 4.060, 4.062, 4.063, 4.068, 4.069, 4.07, 4.073, 4.075, 4.078, 4.079, 4.08 0, 4.081, 4.083, 4.085, 4.089, 4.091, 4.095, 4.096, 4.098 or 4.1, etc., m can be 3.02, 3.03, 3.04 or 3.05, etc., p can be 1.4, 1.45, 1.5, 1.52, 1.55, 1.56, 1.58 or 1.6, etc., q can be 0.8, 0.9, 1.0, 1.1, 1.2, 1.3 or 1.4, etc.
[0063] In the above embodiment, the composite lithium vanadium phosphate material of the coating layer of the lithium-rich material contains both pyrophosphate and phosphate while providing ion channels and capacity, and the ratio of the two is appropriate. The ionic conductivity of the composite lithium vanadium phosphate material is improved by doping with anions, and the water absorption of pyrophosphate is utilized to avoid hydrolysis of the lithium-rich lithium ferrite material due to water absorption and the sharp attenuation of the electrochemical performance, which is beneficial to improving the lithium supplement effect.
[0064] In some embodiments, the molar ratio of the lithium-rich lithium ferrite material to the composite lithium vanadium phosphate material is 1:(0.05-0.3).
[0065] In the above embodiment, by controlling the amount ratio of the lithium-rich lithium ferrite material to the composite lithium vanadium phosphate material within the range of 1: (0.05-0.3), the ratio of the core to the coating layer of the lithium supplement agent is appropriate, and the protective effect of the coating layer on the core is fully utilized to improve the stability of the lithium supplement agent while maintaining a high capacity of the lithium supplement agent.
[0066] For example, the amount ratio of the lithium-rich lithium ferrite material to the composite lithium vanadium phosphate material can be 1:0.05, 1:0.1, 1:0.12, 1:0.13, 1:0.15, 1:0.17, 1:0.18, 1:0.19, 1:0.2, 1:0.25 or 1:0.3, etc.
[0067] In some embodiments, the amount ratio of the lithium-rich lithium ferrite material to the composite lithium vanadium phosphate material is 1: (0.1-0.3). By controlling the amount ratio of the lithium-rich lithium ferrite material to the composite lithium vanadium phosphate material within the range of 1: (0.1-0.3), it is beneficial to utilize the coating layer to improve the stability of the lithium supplement agent, while making the lithium supplement agent have a higher charge specific capacity and discharge specific capacity when used in a secondary battery, thereby having a better lithium supplement effect.
[0068] In some embodiments, the amount ratio of the lithium-rich lithium iron oxide material to the composite lithium vanadium phosphate material is 1: (0.1-0.2). By controlling the amount ratio of the lithium-rich lithium iron oxide material to the composite lithium vanadium phosphate material within the range of 1: (0.1-0.2), it is beneficial to further improve the charge specific capacity and discharge specific capacity of the lithium supplement when applied to the secondary battery, thereby having a better lithium supplement effect.
[0069] In some embodiments, the D10 particle size of the lithium supplement is 1.4 μm to 8.9 μm, the D50 particle size is 3.8 μm to 33.8 μm, and the D90 particle size is 7.9 μm to 48.7 μm. The D10 particle size, D50 particle size, and D90 particle size of the lithium supplement are measured by a laser particle size analyzer, wherein the D10 particle size indicates the particle size corresponding to when the cumulative volume distribution percentage of the lithium supplement reaches 10%, the D50 particle size indicates the particle size corresponding to when the cumulative volume distribution percentage of the lithium supplement reaches 50%, and the D90 particle size indicates the particle size corresponding to when the cumulative volume distribution percentage of the lithium supplement reaches 90%.
[0070] For example, the D10 particle size of the lithium supplement may be 1.4 μm, 1.5 μm, 1.8 μm, 2.0 μm, 2.3 μm, 2.5 μm, 2.7 μm, 2.9 μm, 3.1 μm, 3.2 μm, 3.5 μm, 3.7 μm, 3.9 μm, 4.1 μm, 4.2 μm, 4.5 μm, 4.8 μm, 5.0 μm, 5.3 μm, 5.5 μm, 5.7 μm, 5.9 μm, 6.1 μm, 6.2 μm, 6.5 μm, 6.7 μm, 6.9 μm. , 7.1μm, 7.2μm, 7.5μm, 7.9μm, 8.1μm, 8.2μm, 8.3μm, 8.5μm or 8.9μm, etc.; the D50 particle size of the lithium supplement can be 3.8μm, 4.0μm, 4.5μm, 4.8μm, 5.0μm, 5.3μm, 5.8μm, 6.0μm, 6.8μm, 7.8μm, 8.5μm, 9.0μm, 9.3μm, 10.5μm, 10.9μm, 11μm, 11.2μm, 11.5μm, 11.8μm, 12μm, 12.5μm, 12. 6μm, 12.9μm, 13.5μm, 14μm, 14.2μm, 14.5μm, 14.8μm, 14.9μm, 15.2μm, 16.5μm, 17μm, 17.5μm, 18μm, 18.3μm, 18.4μm, 19μm, 19.5μm, 20μm, 21μm, 21.8μm, 22μm, 22.5μm, 22.7μm, 23μm, 23.5μm, 23.8μm, 24μm, 24.2μm, 24.5μm, 24.8μm, 24.9μm, 25.3μm, The D90 particle size of the lithium supplement agent can be 7.9 μm, 8.0 μm, 8.5 μm, 8.8 μm, 9.0 μm, etc. m, 9.3μm, 9.8μm, 10.0μm, 10.8μm, 10.9μm, 11.5μm, 12.0μm, 12.3μm, 12.5μm, 12.9μm, 13μm, 13.2μm, 13.5μm, 13.8μm, 14μm, 14.5μm, 14.6μm, 14.9μm, 15.5μm, 16μm, 16.2μm, 16.5μm, 16.8μm, 16.9μm, 17.2μm, 17.5μm, 18μm, 18.5μm, 19μm, 19.3μm, 19.4μm, 20μm, 20.5μm, 21μm, 22μm, 22.8μm, 23μm, 23.5μm, 23.7μm, 24μm, 24.5μm, 24.8μm, 25μm, 25.2μm, 25.5μm, 25.8μm, 25.9μm, 26.3μm, 26.5μm, 26.7μm, 26. 9μm, 27.4μm, 27.6μm, 27.8μm, 28μm, 28.5μm, 29μm, 30μm, 30.8μm, 31μm, 31.5μm m, 31.7μm, 32μm, 32.5μm, 32.6μm, 33μm, 33.4μm, 33.8μm, 34μm, 34.1μm, 34.2μm , 34.5μm or 34.8μm, 35μm, 35.3μm, 35.4μm, 36μm, 36.5μm, 37μm, 38μm, 38.8μm, 3 9μm, 39.5μm, 39.7μm, 40μm, 40.5μm, 40.8μm, 41μm, 41.2μm, 41.5μm, 41.8μm, 41 .9μm, 42.3μm, 42.5μm, 42.7μm, 42.9μm, 43.4μm, 43.6μm, 43.8μm, 44μm, 44.5μm m, 45μm, 46μm, 46.8μm, 47μm, 47.5μm, 47.7μm, 48μm, 48.5μm, 48.6μm or 48.7μm, etc. .
[0071] In some embodiments, the compacted density of the lithium supplement is 3.22 g / mL to 3.39 g / mL, and the specific surface area of the lithium supplement is 5.61 m 2 / g ~6.28 m 2 / g. The lithium supplement agent has a high compaction density and a suitable surface area. It has a high energy density and a suitable contact area with the electrolyte when used in a secondary battery, which is beneficial to improving the lithium supplement effect.
[0072] For example, the compacted density of the lithium supplement may be 3.22 g / mL, 3.25 g / mL, 3.3 g / mL, 3.35 g / mL or 3.39 g / mL, etc. The specific surface area of the lithium supplement may be 5.61 m 2 / g, 5.65 m 2 / g, 5.75 m 2 / g, 5.85 m 2 / g, 5.95 m 2 / g, 6.05 m 2 / g, 6.15 m 2 / g, 6.25 m 2 / g or 6.28 m 2 / g, etc.
[0073] In some embodiments, the free lithium content (by mass concentration) of the lithium supplement is less than 300 ppm.
[0074] In some embodiments, the free lithium content of the lithium supplement is 201 ppm to 289 ppm.
[0075] For example, the free lithium content of the lithium supplement can be 201ppm, 205ppm, 210ppm, 215ppm, 220ppm, 225ppm, 230ppm, 235ppm, 240ppm, 245ppm, 250ppm, 255ppm, 260ppm, 265ppm, 270ppm, 275ppm, 280ppm, 285ppm or 289ppm, etc.
[0076] In some embodiments, the water content (by mass concentration) of the lithium supplement is less than or equal to 300 ppm.
[0077] In some embodiments, the water content of the lithium supplement is 200 ppm to 300 ppm, for example, it can be 202 ppm, 212 ppm, 220 ppm, 240 ppm, 260 ppm, 275 ppm, 290 ppm, 297 ppm, etc.
[0078] Controlling the free lithium content and water content of the lithium supplement is beneficial to maintaining the stability and safety of the lithium supplement and improving the lithium supplement effect of the lithium supplement when used in secondary batteries.
[0079] In some embodiments, under the conditions of 25°C and 8% humidity, the first charge specific capacity of the lithium supplement at a rate of 0.1C is 680mAh / g~699mAh / g, preferably 688mAh / g~699mAh / g; the first discharge specific capacity of the lithium supplement at a rate of 0.1C is 24mAh / g~90mAh / g, preferably 24.7mAh / g~89.5mAh / g, and more preferably 43.2mAh / g~68.5mAh / g.
[0080] For example, the first charge specific capacity of the lithium supplement at a rate of 0.1C is 688.1 mAh / g, 682 mAh / g, 683 mAh / g, 685 mAh / g, 687 mAh / g, 689 mAh / g, 690 mAh / g, 695 mAh / g or 698.7 mAh / g, etc., and the first discharge specific capacity of the lithium supplement at a rate of 0.1C can be 24.7 mAh / g, 28 mAh / g, 30 mAh / g, 32 mAh / g, 35 mAh / g, 40 mAh / g, 45 mAh / g, 50 mAh / g, 55 mAh / g, 60 mAh / g, 65 mAh / g, 70 mAh / g, 75 mAh / g, 80 mAh / g, 85 mAh / g or 89.5 mAh / g, etc.
[0081] In some embodiments, the first charge specific capacity of the lithium supplement at a 1C rate is 670 mAh / g to 682 mAh / g, preferably 670.4 mAh / g to 681.1 mAh / g; the first discharge specific capacity of the lithium supplement at a 1C rate is 19.8 mAh / g to 86.1 mAh / g, preferably 19.8 mAh / g to 86.1 mAh / g, and more preferably 40.5 mAh / g to 65.4 mAh / g.
[0082] For example, the first charge specific capacity of the lithium supplement at 1C rate is 669.5 mAh / g, 670 mAh / g, 672 mAh / g, 675 mAh / g, 678 mAh / g, 680 mAh / g or 681.1 mAh / g, etc., and the first discharge specific capacity of the lithium supplement at 1C rate can be 19.8 mAh / g, 20 mAh / g, 25 mAh / g, 30 mAh / g, 35 mAh / g, 40 mAh / g, 45 mAh / g, 50 mAh / g, 55 mAh / g, 60 mAh / g, 65 mAh / g, 70 mAh / g, 75 mAh / g, 80 mAh / g, 85 mAh / g or 86.1 mAh / g, etc.
[0083] In some embodiments, the lithium supplement has a discharge specific capacity of 17 mAh / g to 85 mAh / g, preferably 17.8 mAh / g to 84.1 mAh / g, and more preferably 32.4 mAh / g to 60.7 mAh / g, after 10 charge and discharge cycles at a 1C rate.
[0084] For example, the discharge specific capacity of the lithium supplement after 10 charge and discharge cycles at a 1C rate can be 17.8 mAh / g, 20 mAh / g, 24.7 mAh / g, 28 mAh / g, 30 mAh / g, 32 mAh / g, 35 mAh / g, 40 mAh / g, 45 mAh / g, 50 mAh / g, 55 mAh / g, 60 mAh / g, 65 mAh / g, 70 mAh / g, 75 mAh / g, 80 mAh / g or 84.1 mAh / g, etc.
[0085] In some embodiments, after being placed under the conditions of 25±1°C and 85±5% humidity for 4 hours, the lithium supplement has a first charge specific capacity of 680mAh / g~697mAh / g at a rate of 0.1C, preferably 682mAh / g~697mAh / g; after being placed under the conditions of 25±1°C and 85±5% humidity for 4 hours, the lithium supplement has a first discharge specific capacity of 21mAh / g~90mAh / g at a rate of 0.1C, preferably 42.1mAh / g~67.5mAh / g.
[0086] In some embodiments, after being placed under the conditions of 25±1°C and 85±5% humidity for 12 hours, the lithium supplement has a first charge specific capacity of 677mAh / g~695mAh / g at a rate of 0.1C; after being placed under the conditions of 25±1°C and 85±5% humidity for 12 hours, the lithium supplement has a first discharge specific capacity of 20mAh / g~89mAh / g at a rate of 0.1C, preferably 41mAh / g~68mAh / g.
[0087] In some embodiments, after being placed under the conditions of 25±1°C and 85±5% humidity for 24 hours, the lithium supplement has a first charge specific capacity of 673mAh / g~694mAh / g at a rate of 0.1C; after being placed under the conditions of 25±1°C and 85±5% humidity for 24 hours, the lithium supplement has a first discharge specific capacity of 19mAh / g~89mAh / g at a rate of 0.1C, preferably 41mAh / g~67.1mAh / g.
[0088] In some embodiments, after being placed under the conditions of 25±1°C and 85±5% humidity for 48 hours, the lithium supplement has a first charge specific capacity of 670mAh / g~693mAh / g at a rate of 0.1C; after being placed under the conditions of 25±1°C and 85±5% humidity for 48 hours, the lithium supplement has a first discharge specific capacity of 18mAh / g~89mAh / g at a rate of 0.1C, preferably 41mAh / g~67mAh / g.
[0089] In some embodiments, after being placed under the conditions of 25±1°C and 85±5% humidity for 4 hours, the lithium supplement has a first charge specific capacity of 669mAh / g~680mAh / g at a rate of 1C, preferably 669mAh / g~679mAh / g; after being placed under the conditions of 25±1°C and 85±5% humidity for 4 hours, the lithium supplement has a first discharge specific capacity of 18mAh / g~86mAh / g at a rate of 1C, preferably 36.3mAh / g~65.1mAh / g.
[0090] In some embodiments, after being placed under the conditions of 25±1°C and 85±5% humidity for 12 hours, the lithium supplement has a first charge specific capacity of 664mAh / g~678mAh / g at a 1C rate; after being placed under the conditions of 25±1°C and 85±5% humidity for 12 hours, the lithium supplement has a first discharge specific capacity of 17mAh / g~86mAh / g at a 1C rate, preferably 35mAh / g~65mAh / g.
[0091] In some embodiments, after being placed under the conditions of 25±1°C and 85±5% humidity for 24 hours, the lithium supplement has an initial charge capacity of 661mAh / g to 676mAh / g at a rate of 1C; after being placed under the conditions of 25±1°C and 85±5% humidity for 24 hours, the lithium supplement has an initial discharge capacity of 16mAh / g to 86mAh / g, preferably 34mAh / g to 65mAh / g.
[0092] In some embodiments, after being placed under the conditions of 25±1°C and 85±5% humidity for 48 hours, the lithium supplement has a first charge specific capacity of 653mAh / g~676mAh / g at a rate of 1C, preferably 660mAh / g~676mAh / g; after being placed under the conditions of 25±1°C and 85±5% humidity for 48 hours, the lithium supplement has a first discharge specific capacity of 15mAh / g~85.5mAh / g at a rate of 1C, preferably 34mAh / g~65mAh / g.
[0093] In some embodiments, the above-mentioned first charge specific capacity and first discharge specific capacity of the lithium supplement agent are obtained by preparing a positive electrode sheet having the lithium supplement agent, assembling the positive electrode sheet into a button battery and conducting testing.
[0094] In some embodiments, the positive electrode plate includes a positive electrode active material, a binder and a conductive agent. The positive electrode active material is a lithium supplement as described above. The binder is preferably PVDF (polyvinylidene fluoride), and other adhesive materials suitable for positive electrode plates can also be used. The conductive agent is preferably a carbon conductive material, such as conductive carbon black (SP). The above-mentioned positive electrode active material, binder, and conductive agent are proportioned in a suitable mass ratio, and an aluminum sheet is used as a current collector to prepare a positive electrode plate. The mass ratio of the positive electrode active material, binder, and conductive agent can be 78:8:14.
[0095] In a second aspect, the present application provides a method for preparing a lithium supplement, such as Figure 1 As shown, including:
[0096] S11, provide kernel;
[0097] S12, forming a coating layer on the surface of the inner core to obtain a lithium supplement;
[0098] The lithium supplement comprises a core and a coating layer coated on the surface of the core, the core comprises a lithium-rich lithium ferrite material, and the material of the coating layer comprises a composite lithium vanadium phosphate material.
[0099] In the preparation method of the lithium supplement provided in the embodiment of the present application, a coating layer is formed on the surface of the lithium-rich ferrite material. Since the material of the coating layer includes: a composite lithium vanadium phosphate material, the composite lithium vanadium phosphate material is coated on the surface of the lithium-rich ferrite material. The composite lithium vanadium phosphate material protects the lithium-rich ferrite material, hinders the contact between the lithium-rich ferrite material and the air, and is beneficial to improve the stability and safety of the lithium supplement; at the same time, compared with the carbon material coated on the surface of the lithium-rich ferrite material, the composite lithium vanadium phosphate material not only has better conductivity, but also provides partial capacity, thereby effectively improving the stability of the lithium-rich ferrite material, while also providing ion conduction channels and capacity, significantly improving the lithium supplement effect, and thereby improving the electrochemical performance of the positive electrode sheet, secondary battery and electrical device using the lithium supplement. At the same time, the preparation method of forming a composite lithium vanadium phosphate material on the surface of the lithium-rich ferrite material is simple and easy to implement.
[0100] The lithium-rich lithium ferrite material can be obtained through commercial channels or homemade, which is not specifically limited here.
[0101] The composite lithium vanadium phosphate material is an ion conductor material. When used in a secondary battery, it provides a portion of the capacity while providing a channel for lithium ions to be embedded and de-embedded, allowing the movement of lithium ions during the charge-discharge process.
[0102] In some embodiments, the method for preparing a lithium supplement provided in the present application is used to prepare the lithium supplement as described above.
[0103] In some embodiments, S11, providing a kernel, may include:
[0104] The first lithium salt and the first iron source are mixed and subjected to a first calcination treatment to obtain the lithium-rich lithium ferrite material.
[0105] Wherein, the first lithium salt includes: at least one of lithium sulfite and lithium bisulfite, and the first iron source includes: at least one of red iron oxide, iron oxyhydroxide, iron hydroxide, ferrous oxalate and ferric citrate.
[0106] In the above embodiment, the above lithium salt is used as the raw material of the first lithium salt. Compared with other lithium sources such as lithium oxide and lithium carbonate, the cost is lower and the decomposition temperature is lower, thereby avoiding the problem of insufficient purity caused by absorbing the decomposition gas when synthesizing lithium-rich lithium iron oxide at high temperature.
[0107] In some embodiments, the molar ratio of the lithium element in the first lithium salt to the iron element in the first iron source may be (5.05-5.2):1, so that the first lithium salt and the first iron source fully react to obtain lithium-rich lithium ferrate. For example, the molar ratio of the lithium element in the first lithium salt to the iron element in the first iron source may be 5.05:1, 5.1:1, 5.15:1 or 5.2:1, etc.
[0108] Taking the case where the first lithium salt is lithium sulfite and the first iron source is red iron oxide as an example, the reaction equation for the reaction of lithium sulfite and red iron oxide to generate lithium-rich lithium ferrate material is as shown in the following formula (1):
[0109] 5Li 2 SO 3 +Fe 2 O 3 →2Li 5 FeO 4 +5SO 2 Formula (1)
[0110] In some embodiments, when preparing the lithium-rich lithium iron oxide material, the temperature of the first calcination treatment can be 400° C. to 600° C., and the time can be 4 hours to 12 hours. Controlling the temperature, reaction time and oxygen content of the first calcination treatment can help prevent the lithium-rich lithium iron oxide material from absorbing the gas generated during the first calcination treatment at a higher temperature while the lithium-rich lithium iron oxide material is fully generated, thereby helping to improve the purity and stability of the lithium supplement.
[0111] For example, the temperature of the first calcination treatment can be 400°C, 420°C, 450°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, 560°C, 570°C, 580°C, 590°C or 600°C, and the time can be 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h or 12h, etc.
[0112] In some embodiments, in order to further reduce the impact of oxygen on the stability of the lithium-rich lithium ferrite material, the oxygen content of the first calcination treatment is less than 100 ppm. Specifically, the first calcination treatment can be performed in a calcination furnace with an oxygen content of less than 100 ppm.
[0113] In some embodiments, during the first calcination process, the preparation method further includes: removing waste gas generated by the first calcination process, so that the humidity of the first calcination process is ≤0.5%. Controlling the humidity of the first calcination process and timely removing the waste gas generated during the first calcination process are conducive to improving the stability and purity of the lithium-rich lithium ferrite material.
[0114] For example, when the first calcination process is performed in a calcination furnace, the oxygen content in the calcination furnace can be controlled to be less than 100 ppm by introducing a protective gas into the calcination furnace for the first calcination process, and the humidity in the calcination furnace can be controlled to be less than 0.5% by extracting the gas in the calcination furnace for the first calcination process. The protective gas can include, for example, nitrogen, argon and / or helium.
[0115] In some embodiments, the specific implementation method of forming the coating layer on the surface of the lithium-rich lithium iron oxide material is not limited, and all preparation methods that can coat lithium vanadium phosphate on the surface of the lithium-rich lithium iron oxide material are within the protection scope of this application.
[0116] In some embodiments, S12, the step of forming a coating layer on the surface of the core to obtain a lithium supplement may include:
[0117] S121, providing a dispersion liquid containing lithium iron oxide-rich material;
[0118] S122, dissolving the second lithium salt, the first vanadium salt and the pyrophosphate source in the dispersion, and subjecting the dispersion to a first drying process to obtain a first material;
[0119] S123, the first material is subjected to a second calcination treatment to obtain a lithium supplement agent.
[0120] The second lithium salt includes at least one of lithium acetate, lithium gluconate and lithium nitrate, the first vanadium salt includes at least one of vanadium chloride and vanadium acetate, and the pyrophosphate source includes at least one of pyrophosphate, ammonium monohydrogen pyrophosphate and ammonium dihydrogen pyrophosphate;
[0121] By preparing a dispersion of lithium iron oxide-rich material, dissolving the second lithium salt, the first vanadium salt and the pyrophosphate source in the dispersion, and then performing a first drying treatment, on the one hand, the second lithium salt, the first vanadium salt and the pyrophosphate source are uniformly mixed with the lithium iron oxide-rich material in the form of a solution, and on the other hand, the first drying treatment is used to remove the solvent, so that the second lithium salt, the first vanadium salt and the pyrophosphate source are mixed and uniformly wrapped on the surface of the lithium iron oxide-rich material, and a mixed material layer of the second lithium salt, the first vanadium salt and the pyrophosphate source is formed on the surface of the lithium iron oxide-rich material, so that the second lithium salt, the first vanadium salt and the pyrophosphate source are easily sintered in situ to obtain a coating layer in the second calcination treatment. When the above-mentioned second lithium salt, first vanadium salt and pyrophosphate source materials are used, it is beneficial for the gas generated by the reaction to volatilize at a lower temperature during the second calcination treatment. At the same time, the above-mentioned pyrophosphate source material is used to participate in the preparation of the composite lithium vanadium phosphate material, which absorbs part of the water vapor to become phosphate during the second calcination treatment. While obtaining the anion-doped composite lithium vanadium phosphate material, the water vapor in the atmosphere is effectively dried, avoiding the hydrolysis of the lithium-rich lithium ferrite material due to water absorption, which is beneficial to effectively improve the lithium replenishment effect of the lithium replenisher.
[0122] In some embodiments, the molar ratio of the lithium element in the second lithium salt, the vanadium element in the first vanadium salt, and the pyrophosphate ion in the pyrophosphate source is (3.02-3.05):2:(1.5-1.6), which is conducive to the full reaction of the three to obtain a composite lithium vanadium phosphate material.
[0123] For example, the molar ratio of the lithium element in the second lithium salt, the vanadium element in the first vanadium salt and the pyrophosphate in the pyrophosphate source can be 3.02:2:1.5, 3.02:2:1.55|, 3.02:2:1.6, 3.03:2:1.5, 3.03:2:1.55, 3.03:2:1.6, 3.04:2:1.5, 3.04:2:1.55|, 3.04:2:1.6, 3.05:2:1.5, 3.05:2:1.55 or 3.05:2:1.6, etc.
[0124] Taking the above-mentioned second lithium salt as lithium acetate, the first vanadium salt as vanadium chloride, and the pyrophosphate source as pyrophosphate as an example, the reaction equation of lithium acetate, vanadium chloride and pyrophosphate is shown in the following formula (2):
[0125] CH 3 COOLi+VCl 3 +H 4 P 2 O 7 →Li 3 V 2 (PO 4 ) 3 +HCl+CH3 COOH Formula (2)
[0126] In some embodiments, the solvent used in the above dispersion can be anhydrous ethanol. Anhydrous ethanol has a suitable boiling point, low toxicity, and is more conducive to reducing the hydrolysis of lithium-rich ferrite than water as a solvent. It is suitable as a solvent in the dispersion to disperse the lithium-rich ferrite material, dissolve the second lithium salt, the first vanadium salt and the pyrophosphate source, and improve the stability of the lithium supplement.
[0127] In some embodiments, the mass of anhydrous ethanol used as a solvent for the dispersion can be 5 to 10 times the total mass of the second lithium salt, the first vanadium salt and the pyrophosphate source to fully dissolve the second lithium salt, the first vanadium salt and the pyrophosphate source.
[0128] In some embodiments, the first drying process is spray drying, which is beneficial for effectively controlling the particle size of the first material.
[0129] In some embodiments, the particle size of the first material obtained by spray drying may be 5 μm to 25 μm.
[0130] Optionally, during spray drying, the solvent vapor generated by the spraying can be recovered by condensation and then recycled.
[0131] In some embodiments, the water content (by mass concentration) of the solvent used in the above dispersion is less than 100 ppm, which reduces the introduction of water and helps to avoid hydrolysis of the lithium-rich lithium ferrite material and attenuation of the electrochemical performance.
[0132] In some embodiments, the water content (by mass concentration) of the second lithium salt, the first vanadium salt and the pyrophosphate source is less than 100 ppm, which is beneficial to further reduce the introduction of water and further avoid the hydrolysis of the lithium-rich lithium ferrite material and the attenuation of the electrochemical performance.
[0133] In some embodiments, after dissolving the second lithium salt, the first vanadium salt and the pyrophosphate source in the dispersion, the preparation method of the lithium supplement further includes: grinding the dispersion so that the particle size of the lithium-rich ferrite material in the dispersion is 300nm~500nm. The particle size of the lithium-rich ferrite material after grinding is controlled within 300nm~500nm, and a lithium-rich ferrite material with a small particle size and a concentrated particle size distribution is obtained, which facilitates the uniform deposition of the blended material layer on the surface of the lithium-rich ferrite material, thereby facilitating the acquisition of a lithium supplement with uniform and complete coating.
[0134] In some embodiments, the temperature of the second calcination treatment is 600°C to 700°C, and the time is 3 h to 6 h. For example, the temperature of the second calcination treatment can be 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, 660°C, 670°C, 680°C, 690°C or 700°C, and the time can be 3 h, 4 h, 5 h or 6 h. Controlling the temperature and time of the second calcination treatment is conducive to the full reaction of the composite lithium vanadium phosphate material.
[0135] In some embodiments, the oxygen content of the second calcination treatment is less than 500 ppm, which is beneficial to reduce the contact between oxygen and the lithium supplement agent during the second calcination treatment, and is beneficial to improve the stability and purity of the lithium supplement agent.
[0136] In some embodiments, the second calcination process is performed in a calcination furnace, and the oxygen content in the calcination furnace for the second calcination process is controlled to be lower than 500 ppm accordingly. When the second calcination process is performed in a calcination furnace, the oxygen content in the calcination furnace can be controlled to be lower than 500 ppm by introducing a protective gas into the calcination furnace for the second calcination process. The protective gas can include, for example, nitrogen, argon and / or helium.
[0137] In some embodiments, during the second calcination treatment, the preparation method further includes: removing the waste gas generated by the second calcination treatment, so that the humidity of the second calcination treatment is ≤0.5%. Controlling the humidity of the second calcination treatment and promptly removing the waste gas generated during the second calcination treatment is beneficial to reducing the contact between oxygen, water vapor and waste gas generated by the reaction and the lithium supplement agent during the second calcination treatment, improving the purity and stability of the lithium supplement agent, thereby improving the lithium supplement effect of the lithium supplement agent. Specifically, when the second calcination treatment is carried out in a calcination furnace, the humidity in the calcination furnace can be controlled to be less than 0.5% by pumping out the gas in the calcination furnace.
[0138] After the second calcination treatment is completed, the material obtained from the second calcination treatment can be screened, iron removed and packaged to obtain a lithium supplement. The screening, iron removal and packaging can be performed in a constant temperature and humidity environment, for example, the temperature in the constant temperature and humidity room is 20~30°C and the humidity is ≤5%. Iron removal can be performed using an electromagnetic iron remover, and the magnetic field strength of the electromagnetic iron remover can be 10000 GS~15000GS. After iron removal, the magnetic substance content of the lithium supplement can be less than 1ppm.
[0139] In a third aspect, an embodiment of the present application provides a positive electrode plate, comprising a current collector, and a positive electrode material disposed on at least one side of the current collector along its thickness direction, wherein the positive electrode material comprises the lithium supplement agent as described in the first aspect.
[0140] In the positive electrode plate provided in the embodiment of the present application, the positive electrode plate contains the above-mentioned lithium supplement agent, which includes: a lithium-rich lithium iron oxide material and a composite lithium vanadium phosphate material coated on the surface of the lithium-rich lithium iron oxide material. The composite lithium vanadium phosphate material protects the lithium-rich lithium iron oxide material, hinders the contact between the lithium-rich lithium iron oxide material and the air, which is beneficial to improving the stability and safety of the lithium supplement agent; at the same time, compared with the carbon material coated on the surface of the lithium-rich lithium iron oxide material, the composite lithium vanadium phosphate material not only has better conductivity, but also provides partial capacity, thereby effectively improving the stability of the lithium-rich lithium iron oxide material while also providing ion conduction channels and capacity, significantly improving the lithium supplement effect, and therefore, is beneficial to improving the electrochemical performance of the positive electrode plate.
[0141] In a fourth aspect, an embodiment of the present application provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator; wherein the positive electrode sheet may be the positive electrode sheet described in the third aspect.
[0142] In the secondary battery provided in the embodiment of the present application, the secondary battery includes the above-mentioned positive electrode plate. Since the lithium replenisher in the positive electrode plate has significantly improved lithium replenishment effect, stability and safety, the electrochemical performance of the secondary battery in terms of capacity, stability and safety are all improved.
[0143] In a fifth aspect, an embodiment of the present application provides an electrical device comprising a plurality of batteries connected in series and / or in parallel, wherein at least one battery is a secondary battery as described in the fourth aspect.
[0144] In the electrical device provided in the embodiment of the present application, the electrical device includes the above-mentioned secondary battery. Since the electrochemical properties of the secondary battery in terms of capacity, stability, etc. are all improved, the use stability and safety stability of the electrical device can be effectively improved.
[0145] The electric device provided in the embodiment of the present application may be, but is not limited to, a mobile phone, a tablet, a laptop computer, an electric toy, an electric tool, a battery car, an electric car, a ship, a spacecraft, etc. Among them, the electric toy may include a fixed or mobile electric toy, such as a game console, an electric car toy, an electric ship toy, and an electric airplane toy, etc., and the spacecraft may include an airplane, a rocket, a space shuttle, and a spacecraft, etc.
[0146] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.
[0147] Example 1
[0148] The preparation method of the lithium supplement provided in Example 1 is as follows:
[0149] Step 1), lithium sulfite (i.e., the first lithium salt) and red iron oxide (i.e., the first iron source) are mixed at a molar ratio of 5.1:1, and calcined at 500°C for 8 hours under nitrogen protection to obtain a lithium-rich lithium ferrate material; wherein, during the calcination process, nitrogen is introduced so that the oxygen content in the calcination furnace is less than 100 ppm, and the waste gas generated by the calcination is extracted so that the humidity is less than 0.5%;
[0150] Step 2), adding the lithium-rich lithium iron oxide material to anhydrous ethanol, the water content of which is less than 100 ppm, and then adding dried lithium acetate (i.e., the second lithium salt), vanadium chloride (i.e., the first vanadium salt) and pyrophosphate (i.e., the pyrophosphate source), wherein the amount of substance ratio between the lithium element in lithium acetate, the vanadium element in vanadium chloride and the pyrophosphate in pyrophosphate is 3.04:2:1.55, and the water content of lithium acetate, vanadium chloride and pyrophosphate is less than 100 ppm, adding ceramic balls for grinding, stirring and slurrying, so that lithium acetate, vanadium chloride and pyrophosphate are completely dissolved, and the particle size of the lithium-rich lithium iron oxide material in the slurry is 425 nm, and then spray drying is performed to obtain a spray-dried material (i.e., the first material) with a particle size of 13.5 μm, and the ethanol vapor generated by the spray is recycled after condensation recovery; wherein the mass of anhydrous ethanol is 9 times the total mass of lithium acetate, vanadium trichloride and pyrophosphate;
[0151] Step 3), placing the spray-dried material in a calcining furnace with an oxygen content of less than 500ppm (nitrogen is introduced to replace the air) for calcining at a temperature of 660°C for 5 hours. During the calcining process, the waste gas generated by the calcination is removed so that the humidity in the calcining furnace is ≤0.5%;
[0152] Step 4), after the calcination is completed, the calcined material is screened and iron-removed, and then vacuum-packed. The screening, iron-removal and packaging are carried out in a constant temperature and humidity room (temperature is 25±5°C, humidity ≤5%). The iron removal is carried out by an electromagnetic iron remover with a magnetic field strength of 13000GS. The iron is removed until the content of magnetic substances is less than 1ppm to obtain a lithium supplement, in which the amount ratio of lithium ferrite-rich material (i.e., the core) to composite lithium vanadium phosphate material (i.e., the coating layer) is 1:0.15.
[0153] Example 2
[0154] The preparation method of the lithium supplement provided in Example 2 is substantially the same as the preparation method of the lithium supplement provided in Example 1, except that:
[0155] In step 1), lithium sulfite (i.e., the first lithium salt) and red iron oxide (i.e., the first iron source) are mixed at a molar ratio of 5.05:1, and calcined at 400° C. for 12 h under nitrogen protection to obtain a lithium-rich lithium ferrite material;
[0156] In step 2), the lithium-rich lithium iron oxide material is added to anhydrous ethanol, the water content of which is less than 100 ppm, and then the dried lithium gluconate (i.e., the second lithium salt), vanadium acetate (i.e., the first vanadium salt) and ammonium monohydrogen pyrophosphate (i.e., the pyrophosphate source) are added, wherein the molar ratio of the lithium element in the lithium gluconate, the vanadium element in the vanadium acetate and the pyrophosphate ion in the ammonium monohydrogen pyrophosphate is 3.02:2:1.5, and the water content of the lithium gluconate, the vanadium acetate and the ammonium monohydrogen pyrophosphate is less than 100 ppm, and ceramic balls are added for grinding and stirring to form a slurry, so that the lithium gluconate, the vanadium acetate and the ammonium monohydrogen pyrophosphate are completely dissolved, and the particle size of the lithium-rich lithium iron oxide material in the slurry is 300 nm (i.e., the core), and then spray drying is performed to obtain a spray-dried material (i.e., the first material) with a particle size of 5 μm, and the ethanol vapor generated by the spraying is condensed and recovered for recycling; wherein the mass of the anhydrous ethanol is 5 times the total mass of the lithium gluconate, the vanadium acetate and the ammonium monohydrogen pyrophosphate;
[0157] In step 3), the spray-dried material is placed in a calcining furnace (nitrogen is introduced to replace the air) with an oxygen content of less than 500ppm for calcining at a temperature of 600°C for 3 hours. During the calcining process, the waste gas generated by the calcination is pumped away so that the humidity in the calcining furnace is ≤0.5%;
[0158] In step 4), after the calcination is completed, the calcined material is screened and iron-removed, and then vacuum-packed. The screening, iron-removal and packaging are carried out in a constant temperature and humidity room (temperature is 25±5°C, humidity ≤5%). Iron removal is carried out by an electromagnetic iron remover with a magnetic field strength of 10000GS. The iron is removed until the content of magnetic substances is less than 1ppm to obtain a lithium supplement, in which the amount ratio of lithium ferrite-rich material (i.e., the core) to composite lithium vanadium phosphate material (i.e., the coating layer) is 1:0.15.
[0159] Example 3
[0160] The preparation method of the lithium supplement provided in Example 3 is substantially the same as the preparation method of the lithium supplement provided in Example 1, except that:
[0161] In step 1), lithium sulfite (i.e., the first lithium salt) and red iron oxide (i.e., the first iron source) are mixed at a molar ratio of 5.2:1, and calcined at 600° C. for 4 h under nitrogen protection to obtain a lithium-rich lithium ferrite material;
[0162] In step 2), the lithium iron oxide material is added to anhydrous ethanol, the water content of which is less than 100 ppm, and then lithium nitrate (i.e., the second lithium salt), vanadium chloride (i.e., the first vanadium salt) and ammonium dihydrogen pyrophosphate (i.e., the pyrophosphate source) that have been dried are added, wherein the amount of substance ratio between the lithium element in the lithium nitrate, the vanadium element in the vanadium chloride and the pyrophosphate ion in the ammonium dihydrogen pyrophosphate is 3.05:2:1.6, and the water content of the lithium nitrate, the vanadium chloride and the ammonium dihydrogen pyrophosphate is less than 100 ppm, ceramic balls are added for grinding, and the stirring slurry is made so that the lithium nitrate, the vanadium chloride and the ammonium dihydrogen pyrophosphate are completely dissolved, and the particle size of the lithium iron oxide material in the slurry is 500 nm (i.e., the core), and then spray drying is performed to obtain a spray-dried material (i.e., the first material) with a particle size of 25 μm, and the ethanol vapor generated by the spraying is condensed and recovered for recycling; wherein the mass of the anhydrous ethanol is 10 times the total mass of the lithium nitrate, the vanadium chloride and the ammonium dihydrogen pyrophosphate;
[0163] In step 3), the spray-dried material is placed in a calcining furnace (nitrogen is introduced to replace the air) with an oxygen content of less than 500ppm for calcination at a temperature of 700°C for 6 hours. During the calcination process, the waste gas generated by the calcination is pumped away so that the humidity in the calcining furnace is ≤0.5%;
[0164] In step 4), after the calcination is completed, the calcined material is screened and iron-removed, and then vacuum-packed. The screening, iron-removal and packaging are carried out in a constant temperature and humidity room (temperature is 25±5°C, humidity ≤5%). Iron removal is carried out by an electromagnetic iron remover with a magnetic field strength of 15000GS. The iron is removed until the content of magnetic substances is less than 1ppm to obtain a lithium supplement, in which the amount ratio of lithium ferrite-rich material (i.e., the core) to composite lithium vanadium phosphate material (i.e., the coating layer) is 1:0.15.
[0165] Example 4
[0166] The preparation method of the lithium supplement provided in Example 4 is substantially the same as the preparation method of the lithium supplement provided in Example 1, except that:
[0167] In step 2), the molar ratio of lithium acetate, vanadium chloride and pyrophosphoric acid is 3.00:2:1.55.
[0168] Example 5
[0169] The preparation method of the lithium supplement provided in Example 5 is substantially the same as the preparation method of the lithium supplement provided in Example 1, except that:
[0170] In step 2), the molar ratio of lithium acetate, vanadium chloride and pyrophosphoric acid is 3.03:2:1.65.
[0171] Example 6
[0172] The preparation method of the lithium supplement provided in Example 6 is substantially the same as the preparation method of the lithium supplement provided in Example 1, except that:
[0173] In step 2), lithium acetate, vanadium chloride and pyrophosphate are completely dissolved by grinding, and the particle size of the lithium iron-rich material in the slurry is 250 nm (ie, the core), and then spray-dried to obtain a spray-dried material (ie, the first material) with a particle size of 3 μm.
[0174] Example 7
[0175] The preparation method of the lithium supplement provided in Example 7 is substantially the same as the preparation method of the lithium supplement provided in Example 1, except that:
[0176] In step 2), lithium acetate, vanadium chloride and pyrophosphate are completely dissolved by grinding, and the particle size of the lithium iron-rich material in the slurry is 550 nm (ie, the core), and then spray-dried to obtain a spray-dried material (ie, the first material) with a particle size of 30 μm.
[0177] Example 8
[0178] The preparation method of the lithium supplement provided in Example 8 is substantially the same as the preparation method of the lithium supplement provided in Example 1, except that:
[0179] The amount of material ratio of the lithium-rich lithium ferrite material (i.e. the core) and the composite lithium vanadium phosphate material (i.e. the coating layer) in the lithium supplement is 1:0.1.
[0180] Example 9
[0181] The preparation method of the lithium supplement provided in Example 9 is substantially the same as the preparation method of the lithium supplement provided in Example 1, except that:
[0182] The amount of material ratio of the lithium-rich lithium ferrite material (i.e. the core) and the composite lithium vanadium phosphate material (i.e. the coating layer) in the lithium supplement is 1:0.2.
[0183] Example 10
[0184] The preparation method of the lithium supplement provided in Example 10 is substantially the same as the preparation method of the lithium supplement provided in Example 1, except that:
[0185] The amount of material ratio of the lithium-rich lithium ferrite material (i.e. the core) and the composite lithium vanadium phosphate material (i.e. the coating layer) in the lithium supplement is 1:0.3.
[0186] Embodiment 11
[0187] The preparation method of the lithium supplement provided in Example 11 is substantially the same as the preparation method of the lithium supplement provided in Example 1, except that:
[0188] The amount of material ratio of the lithium-rich lithium ferrite material (i.e. the core) and the composite lithium vanadium phosphate material (i.e. the coating layer) in the lithium supplement is 1:0.05.
[0189] Comparative Example 1
[0190] The preparation method of the lithium supplement provided in Comparative Example 1 is substantially the same as the preparation method of the lithium supplement provided in Example 1, except that:
[0191] The lithium-rich lithium ferrite material prepared in step 1) is directly crushed to a particle size of 2.7 μm and used as a lithium supplement.
[0192] Test methods and test results
[0193] 1. Test of chemical composition and physical and chemical indicators of lithium supplements
[0194] The lithium supplements prepared in Examples 1 to 8 and Comparative Example 1 were tested for chemical composition indexes and physicochemical indexes, and the specific test results are shown in Table 1 below.
[0195] Table 1
[0196]
[0197]
[0198] Among them, in the above Table 1, in the lithium supplement, the Fe content is determined by titanium trichloride reduction potassium dichromate titration method, the lithium content and vanadium content are determined by inductively coupled plasma atomic emission spectrometry, the phosphorus content can be determined by quinoline phosphomolybdic acid weighing method, the chloride ion can be determined by a chloride ion selective electrode, and the free lithium can be determined by automatic potentiometric titration.
[0199] In Table 1, the water content in the lithium supplement is obtained by the KF (Karl Fischer) method; the magnetic foreign matter in the lithium supplement can be collected by a magnet, then dissolved by aqua regia, and tested on an atomic absorption spectrometer; the pH value of the lithium supplement can be used to detect the amount of residual alkali on the surface of the lithium supplement, and is obtained by acid-base potentiometric titration; the specific surface area of the lithium supplement is obtained by the BET specific surface area determination method, such as the gas adsorption multi-point BET method; the D50 particle size, D90 particle size and D10 particle size in the particle size distribution of the lithium supplement are obtained by the laser particle size analyzer, and the laser particle size analyzer is the Mastersizer 3000 laser particle size analyzer of Malvern Instruments Ltd., UK; wherein the D50 particle size indicates the particle size corresponding to the cumulative volume distribution percentage of the lithium supplement reaching 50%, the D10 particle size indicates the particle size corresponding to the cumulative volume distribution percentage of the lithium supplement reaching 10%, and the D90 particle size indicates the particle size corresponding to the cumulative volume distribution percentage of the lithium supplement reaching 90%.
[0200] The powder compaction density (PD) is measured by using a compaction density meter with a test pressure of 3T and a pressing time of 30S.
[0201] It can be seen from Table 1 that the lithium supplement provided in Examples 1 to 8 of the present application, compared with the lithium supplement provided in Comparative Example 1, all of the lithium supplement provided in Examples 1 to 8 have a coating layer of a composite lithium vanadium phosphate material coated on the surface of lithium-rich lithium ferrate, and have a higher specific surface area, such as the specific surface area maintained at 5.61 m2 / g to 6.28 m2 / g; a more suitable pH value, such as the pH value maintained between 9.02 and 9.78; a lower free lithium content, such as the free lithium content maintained between 201 ppm and 375 ppm; This indicates that the lithium supplement provided in Examples 1 to 8 of the present application has better stability, less free lithium content and residual alkali content.
[0202] 2. Electrical performance index test of lithium supplement
[0203] The lithium supplement provided in Examples 1 to 11 and Comparative Example 1 were used as positive electrode active materials, respectively, and SP and PVDF were mixed in a ratio of 78%, 14% and 8% to prepare positive electrode sheets, and the surface density of the positive electrode sheets was 3.6 mg / cm2.
[0204] The positive electrode sheet, separator, negative electrode sheet and electrolyte are assembled into a button battery. The separator is glass fiber, the negative electrode sheet is a metal lithium sheet, the solute of the electrolyte is LiPF6, the solvent is a mixed solvent of EC (ethylene carbonate) and DEC (diethyl carbonate) with a volume ratio of 1:1, and the concentration of LiPF6 is 1 mol / L.
[0205] (1) After the prepared button battery was left standing for 10 hours at room temperature (25°C) and a humidity of 8%, the button battery was activated by charge-discharge. Then, the electrical performance index of the prepared button battery was tested at room temperature (25°C) in the voltage range of 2.00V~4.35V. The nominal gram capacity was 700mAh / g. The charge-discharge test was performed at a rate of 0.1C and 1C, respectively. The specific test results are shown in Table 2 below.
[0206] Table 2
[0207]
[0208] As can be seen from Table 2, the button cells prepared with the lithium supplement provided in Examples 1 to 11 as the positive electrode active material have higher first charge specific capacity and first discharge specific capacity than the button cells prepared with the lithium supplement provided in Comparative Example 1 as the positive electrode active material, indicating that the lithium supplement provided in Examples 1 to 11 effectively protects the lithium-rich lithium ferrate by coating the composite lithium vanadium phosphate material on the surface of the lithium-rich lithium ferrate, enhances the capacity of the lithium supplement, and improves the stability of the lithium supplement. Specifically, the 0.1C first charge specific capacity is above 680 mAh / g, the 0.1C first discharge specific capacity is above 20 mAh / g, the 1C first charge specific capacity is above 670 mAh / g, and the 1C first discharge specific capacity is above 15 mAh / g, which are significantly improved compared with the comparative example 1 in which the 0.1C first charge specific capacity is only 656.3 mAh / g, the 0.1C first discharge specific capacity is only 10.2 mAh / g, the 1C first charge specific capacity is only 631.2 mAh / g, and the 1C first discharge specific capacity is only 6.5 mAh / g.
[0209] By comparing the test results of button batteries prepared by using the lithium supplement provided in Example 1, Example 8 to Example 11 as positive electrode active materials in Table 2, it can be seen that in the lithium supplement provided by the present application, the molar ratio of lithium-rich lithium ferrite to the composite lithium vanadium phosphate material is controlled in the range of 1:0.1 to 1:0.3 to obtain a higher first charge specific capacity and a higher first discharge specific capacity.
[0210] In addition, the button batteries prepared by using the lithium supplement provided in the above Examples 1 to 11 and Comparative Example 1 as positive electrode active materials were cycled 10 times at 1C rate, and the discharge capacity of the button batteries prepared by using the lithium supplement provided in Examples 1 to 11 as positive electrode active materials can still reach more than 15 mAh / g, and can even reach 84.1 mAh / g. However, the button batteries prepared by using the lithium-rich lithium ferrite supplement provided in Comparative Example 1 as positive electrode active materials had a discharge capacity of less than 10 mAh / g after 10 cycles at 1C rate, and had a large capacity attenuation rate, indicating that the lithium-rich lithium ferrite supplement provided in Comparative Example 1 has basically no electrochemical activity and chemical capacity.
[0211] (2) The prepared button battery was placed in an environment with a humidity of 85±5% and a temperature of 25±1°C for 4h, 12h, 24h and 48h and then the electrical performance was tested again. The specific test method was the same as the test method after standing for 10 hours. The test results are shown in Table 3 below:
[0212] Table 3
[0213]
[0214]
[0215] As can be seen from Table 3, compared with the lithium supplement provided in Comparative Example 1, since the lithium-rich lithium ferrate material is not coated with the composite lithium vanadium phosphate material on the surface, the lithium-rich lithium ferrate is hydrolyzed and decomposed when in contact with carbon dioxide and water vapor, resulting in a sharp attenuation of the first charge specific capacity of the button battery using the lithium supplement provided in Comparative Example 1 as the positive electrode active material in a high humidity environment. The button batteries prepared with the lithium supplement provided in Examples 1 to 11 as the positive electrode active material have higher charge specific capacity and higher discharge specific capacity after being placed in an environment with a humidity of 85±5% and a temperature of 25±1°C for 4h, 12h, 24h and 48h. Compared with the results in Table 2 of the button batteries using the lithium supplement provided in each embodiment as the positive electrode active material, the differences in the first charge specific capacity and the first discharge specific capacity are small, indicating that the lithium supplement provided in Examples 1 to 11 has excellent stability, especially stability in a high humidity environment.
[0216] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A lithium supplement, characterized in that: include: A lithium-rich material, comprising a core and a coating layer coated on the surface of the core; Wherein, the core includes: lithium-rich lithium ferrite material, and the material of the coating layer includes: composite lithium vanadium phosphate material.
2. The lithium supplement according to claim 1, characterized in that: The general formula of the lithium-rich material is Li x FeO y @Li m V2(PO4) p (P2O7) q , where x is 5.05~5.2, y is 4.025~4.1, m is 3.02~3.05, p is 1.4~1.6, and q is 0.8~1.
4.
3. The lithium supplement according to claim 1, characterized in that: The amount ratio of the lithium-rich lithium ferrite material to the composite lithium vanadium phosphate material is 1:(0.05-0.3).
4. A method for preparing a lithium supplement, characterized in that: include: Provide the kernel; forming a coating layer on the surface of the core to obtain the lithium supplement; The lithium supplement comprises a core and a coating layer coated on the surface of the core, the core comprises a lithium-rich lithium ferrite material, and the coating layer comprises a composite lithium vanadium phosphate material.
5. The method for preparing a lithium supplement according to claim 4, characterized in that: The steps to provide a kernel include: The first lithium salt and the first iron source are mixed and subjected to a first calcination treatment to obtain the lithium-rich lithium ferrite material; Wherein, the first lithium salt includes: at least one of lithium sulfite and lithium bisulfite, and the first iron source includes: at least one of red iron oxide, iron oxyhydroxide, iron hydroxide, ferrous oxalate and ferric citrate.
6. The method for preparing a lithium supplement according to claim 5, characterized in that: The step of forming a coating layer on the surface of the core to obtain the lithium supplement comprises: Providing a dispersion liquid having the lithium-rich lithium ferrite material; Dissolving a second lithium salt, a first vanadium salt and a pyrophosphate source in the dispersion, and subjecting the dispersion to a first drying process to obtain a first material; The first material is subjected to a second calcination treatment to obtain the lithium supplement agent; The second lithium salt includes at least one of lithium acetate, lithium gluconate and lithium nitrate, the first vanadium salt includes at least one of vanadium chloride and vanadium acetate, and the pyrophosphate source includes at least one of pyrophosphate, ammonium monohydrogen pyrophosphate and ammonium dihydrogen pyrophosphate.
7. The method for preparing a lithium supplement according to claim 6, characterized in that: During the first calcination treatment, the method for preparing the lithium supplement further includes: removing waste gas generated by the first calcination treatment so that the humidity of the first calcination treatment is ≤0.5%; and / or, After dissolving the second lithium salt, the first vanadium salt and the pyrophosphate source in the dispersion, the preparation method of the lithium supplement further comprises: grinding the dispersion so that the particle size of the lithium-rich lithium ferrite material in the dispersion is 300nm~500nm; and / or, During the second calcination treatment, the method for preparing the lithium supplement further includes: removing waste gas generated by the second calcination treatment so that the humidity of the second calcination treatment is ≤0.5%.
8. The method for preparing a lithium supplement according to claim 6, characterized in that: The preparation method of the lithium supplement meets at least one of the following conditions: (1) the molar ratio of the lithium element in the first lithium salt to the iron element in the first iron source is (5.05-5.2):1; (2) The temperature of the first calcination treatment is 400°C to 600°C, and the time is 4h to 12h; (3) The oxygen content of the first calcination treatment is less than 100 ppm, and the oxygen content of the second calcination treatment is less than 500 ppm; (4) the molar ratio of the lithium element in the second lithium salt, the vanadium element in the first vanadium salt and the pyrophosphate ion in the pyrophosphate source is (3.02-3.05):2:(1.5-1.6); (5) The first drying process is spray drying; (6) The water content of the solvent used in the dispersion is less than 100 ppm; (7) The temperature of the second calcination treatment is 600°C to 700°C, and the time is 3 h to 6 h.
9. A positive electrode sheet, characterized in that: It comprises a current collector and a positive electrode material arranged on at least one side of the current collector along the thickness direction thereof, wherein the positive electrode material comprises the lithium supplement agent according to any one of claims 1 to 3 or the lithium supplement agent prepared by the preparation method of the lithium supplement agent according to any one of claims 4 to 8.
10. A secondary battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet and a separator, wherein the positive electrode sheet is the positive electrode sheet as claimed in claim 9.